PENGGUNAAN MEDIA INTERAKTIF DALAM PEMBELAJARAN BAHASA ARAB DI SEKOLAH DASAR - Arrasyid, Saad; Choir, Jihan Alhanin (JAMBURA Elementary Education Journal, 2024)
Abstrak This article discusses the effectiveness of the use of interactive media in learning Arabic in primary schools, focusing on how these media can improve the Arabic language skills of students. Research uses qualitative methods with case studies approaches, involving live observations, interviews with teachers and students, as well as analysis of learning documents. Research results show that interactive media including learning apps, educational games, and animated videos significantly improve student motivation and their language skills. These media make the learning process more exciting and dynamic, as well as engage students actively through a variety of interactive activities. The article explores how interactive media facilitates more efficient and exciting learning, as well as the challenges faced, such as the need for technical support and training for teachers. This article also highlights the implications for teaching Arabic in primary schools, showing that with proper integration, interactive medium can be an innovative solution for improving the quality of learning. Technical support and adequate teacher training are key to maximizing the benefits of interactive media in the language learning process.